"The Path Makes Us Strong": Experiences of Reproductive Coercion Among Latina Women and Strategies for Minimizing Harm. (26th September 2019) - Grace, Karen Trister; Alexander, Kamila A.; Jeffers, Noelene K.; Miller, Elizabeth; Decker, Michele R.; Campbell, Jacquelyn; Glass, Nancy
Abstract : Introduction: Latina women disproportionately report experiencing reproductive coercion (RC), a set of behaviors that interfere with autonomous reproductive decision‐making. Given RC's associations with intimate partner violence (IPV) and unintended pregnancy, it is critical to identify and address RC to assist women to achieve safety, autonomy, and reproductive life plans. The purpose of this study was to describe RC and the use of RC safety strategies among Latina women receiving IPV services at an urban clinic Methods: Qualitative descriptive methodology was used. A purposive sample of 13 Latinas aged 20 to 40 years was recruited. Semi‐structured interviews were transcribed and translated, then read to verify accuracy and gain understanding of overall responses, ensuring confirmability and trustworthiness. Two authors developed a codebook of a priori and emerging codes, and independently applied it. Discrepancies were triangulated with a third researcher, establishing credibility and confirmability. Codes were grouped into theoretical constructs. Results: Themes included RC behaviors (with subthemes pregnancy pressure, birth control sabotage, and controlling pregnancy outcome), co‐occurrence of RC and IPV, and RC harm reduction strategies. New RC behaviors emerged, and immigration status was used as a method of coercive control. Cultural norms emerged as sources of vulnerability and resilience. Coercive partners were also violent. Harm reduction strategies included less detectable contraception; some sought community services, but others resorted to deception and stalling as the only tools available to them. Discussion: The importance of translation services and clearly stating immigration risks from seeking help was apparent. Less detectable methods of contraception remain useful harm reduction strategies. Midwives should inquire about method fit and be mindful of honoring the request when patients ask to change methods. Cultural norms of strength and resilience emerged as vital sources of power and endurance. Nurses and researchers must consider how to support this and help women to access it. This diverse sample and the powerful voices of the women who participated make a significant contribution to the understanding of RC experienced by Latina women in the United States.